The Contribution of Feminist Ethnography to Critical Social Work: Reflections on Research about Child Marriage and FGM - Wariyatun; Qoniah (Pusat Studi Gender Universitas Jember, 2026)
Ethnography is well-known as a research method that is usually applied in anthropology. In its development, social science and humanities researchers have adopted ethnography as their research method. The development program applied ethnography for baseline, monitoring, and evaluation methods. It is applied especially for examining social problems rooted in the socio-cultural context. Translating cultural reflection on field work is a power of ethnography. Ethnography provides a means to describe events, socio-cultural phenomena, and social issues. Those phenomena are analyzed and interpreted from the perspective of the subject of research. This paper argues that ethnography contributes to critical social work studies by translating the cultural meanings behind child marriage and female genital mutilation (FGM) phenomena. It also argues that a feminist approach combined with ethnography can minimize research dilemmas, capture injustice, and unravel the intersectionality inherent in social work. Research on child marriage and FGM requires not only ethnography but also a feminist approach. A feminist approach can explore the power relations between men and women in the issues of FGM and child marriage. Feminist ethnography's methods can uncover power relations and injustices in society. This paper utilizes a critical reflection method for data collection. Applying a critical reflection based on the researcher's experience in research on child marriage and FGM, it is found that ethnography can translate the cultural meanings behind child marriage and FGM. Further findings indicate that a feminist approach combined with ethnography can minimize research dilemmas, capture injustice, and unravel the intersectionality inherent in social work. This study employs critical reflection for data collection. The data analyzed in this paper is the author’s personal experience conducting two research projects in East Nusa Tenggara (NTT) in 2019, and in West Nusa Tenggara (NTB) and East Java in 2025.